SIRT1 performs a balancing act on the tight-rope toward longevity - Purushotham, Aparna (Impact Journals LLC, 2009)
Our recent study defined a new role for SIRT1 as a regulator of hepatic lipid metabolism. In the liver a major target of this sirtuin is the PPARα/PGC-1α signaling axis. Ablation of SIRT1 in the liver results in disrupted fatty acid oxidation, increased cellular stress, and elevations in proinflammatory cytokines. However, contrary to previous studies, we observed no changes in glucose production in the absence of SIRT1, despite impaired PGC-1α signaling. These findings point toward the involvement of other players in SIRT1-regulated hepatic metabolism. Here we discuss our findings, and comment on some of the controversy surrounding this protein in the current literature.